Productive performance and fatty acid profile of hungarian carp fingerlings fed with Spirulina enriched feed (Research, Society and Development, 2020)
The incentive for fish consumption by the population increased its captive breeding production and consequently, increased the demand for feeds. This study aimed at evaluating the use of Spirulina microalga as source of protein, in place of the Saccharomyces cerevisiae yeast, on the productive performance and fatty acid profile of Hungarian carp fingerlings (Cyprinos carpio). In order to carry out this experiment, a basal ration formulated with soybean meal and dehydrated yeast (Control), and other rations formulated with the Spirulina microalga substituting yeast at 25, 50, 75 and 100% levels. 280 Hungarian carp fingerlings with 50 days and average initial live-weight of g were used. The microalgae enriched rations increased linearly the weight gain and the specific growth rate of the fingerlings. The saturated fatty acids represent more than 50% of the lipid content. In relation to the polyunsaturated fatty acids, an increasing rise was observed as the protein substitution of the ration by the microalgae increased.